Effect of botanicals and bioagents on disease intensity and cost-benefit ratio of Sponge Gour (Bulletin of Pure and Applied Sciences – Physics, 2020)
Dye sensitized solar cells (DSSCs) have been intensively investigated. They are  regarded as third generation latest photovoltaic technology in solar cells. This  technology is found to be highly effective for low cost, more efficiency in low light  conditions and its more absorption with different wavelengths across the visible  light spectrum. The DSSC is commonly based on the extracted dye from flowers,  roots and leaves of natural plants and trees. The natural dyes are collected from  plants and trees to be used as natural photosensitizers for DSSCs. The cells are the  fabricated using TiO2 deposited on transparent fluorine doped tin oxide (FTO)  conducting glass plate by using doctor blading method. The optical characteristics of  the extracted dye solutions have been performed in between visible light range of  400nm to 780nm. Its photoelectrochemical performance for the cells has been  studied. The (I-V) characteristic curves of all fabricated cells have been measured  and further analysed for its better performance. Further, the impedance  spectroscopy of the cells has been investigated for best performance analysis.